2+3+3=8
5+1+2=8))))))))))))))))))))
Ответ:
36+23 = 59 , 59-23 = 36 . Проверка: 59-36 = 23 , 23+36= 59
Пошаговое объяснение:
36 + ( 6 + 3 = 9 , 3 + 2 = 5 . Записываем единицы под единицами,
23 десятки под десятками)
------ 59- (9-3 = 6 , записываем под единицами,
59 23 5-2 = 3 , записываем под десятками)
-----
36
9,8х+12,6-27,6=10,1х
9,8х-10,1х=15
-0,3х=15
х=-50
7(1,4*(-50)+1,8)-27,6=10,1*(-50)
7(-70+1,8)-27,6=-505
-505=-505
-2,1х+56+1,2х+15=59,5
-0,9х+71=59,5
-0,9х=59,5+71
-0,9х=130,5
х=130,5/0,9
х=-145
3^x*2^y=12
2*2^y-3^x=5
3^x=2*2^y-5
2^y(2*2^y-5)=12
2*2^2y-5*2^y-12=0
2^y=a
2a^2-5a-12=0
a1=4, 2^y=4,y=2
3^x=2*4-5=3,x=1
Ответ: (1;2)